Effects of organizational culture on innovation: an empirical survey - Vargas-Halabí, Tomas (2016)
The study measured the direct and indirect contribution of organizational cultural traits in innovation performance (IP). A scale for IP was generated and to measure organizational culture the D.O.C.S. scale was adapted. These scales were assessed in a sample of 445 students enrolled in Costa Rica Institute of Technology Master programs who worked as supervisors or managers in manufacturing, commercial and service companies in Costa Rica. SEM was used for latent construct analysis. EQS 6.3 option of maximum likelihood was used for robust statistics estimates. The results were also corroborated by path analysis using scaled scores by means of ordinary least squares provided by Process 2.13. The study showed the positive influence of Mission dimension on Adaptability and this, in turn, in the IP. The suppressive effect of efficiency cultural dimension (Consistency) in the IP was confirmed. Contrary to expectations, the involvement cultural dimension did not show either mediator or direct effect on the IP.